A brief review of the genus Lithosarctia, with the description of a new species from China (Lepidoptera, Erebidae, Arctiinae) - Volynkin, Anton V.; Saldaitis, Aidas; Višinskas, Vytautas (Zootaxa, 2018)
The genus Lithosarctia Daniel, 1954 is revised. A new species, Lithosarctia (Lithosarctia) witti Volynkin & Saldaitis, sp. nov. is described from China (Sichuan Province), together with the description of its biology. The subgenus Ocnogynodes Dubatolov, 1987 is synonymized with Lithosarctia. The female genitalia of Lithosarctia kozlovi Dubatolov, is also described.